PENDIDIKAN KARAKTER DALAM DUNIA PENDIDIKAN - Chairiyah C (LITERASI: Indonesian Journal of Humanities, 2014)
Recently, education character become an interesting topic to be discussed. It is caused by the moral degradation of young generation. Education world through its institution that should create young generation intelectually and morally, in fact, they fail to create their learners with good characters. Actually, education character has been done since Ki Hajar Dewantara era, but then, it is scraped by modernization that destroy many values of nation culture, including education. That's why, education character is urgent in the education world. Character education must be integrated in all subjects, because it is impossible burdening of learning moral and character only on two subjects namely religious education and citizenship education. This paper will discuss about the importance of education character in Indonesia, roles of school, and internalization strategies of education character that can be used by teachers in imparting moral values to the students. Keywords: education character, values, moral, behavior, strategy